Perspectives on music performance anxiety at the university level: a comprehensive guide for educating musicians on effective coping strategies - Phillips, Gabriella (My University, 2025)
This project investigates the cognitive, physiological, and behavioral manifestations of music performance anxiety (MPA) with the goal to create an educational guide of effective coping strategies for musicians. Musicians often face the prevalent obstacle of music performance anxiety (MPA), which can impact their overall well-being and performance quality. I actively experience MPA and understand the various causes and symptoms that come with this challenge. This paper highlights various coping strategies that have been effective for musicians with MPA. I examine different coping mechanisms like mindfulness, and cognitive-behavioral strategies while also practicing performance exposure therapy and deep breathing exercises. Through reviewing the literature, I identified a potential gap within MPA research; musicians often do not learn about MPA through school or private instruction. Without proper training on MPA, teachers are not prepared to handle those symptoms and students miss out on the support and guidance they seek. Throughout this project, I have learned four overarching coping mechanisms that are accompanied by smaller, practical techniques that support their effectiveness: preparation, student/teacher relationships, performance practice, and breathing exercises.
Keywords: Music performance anxiety; Self-efficacy; Exposure therapy; Somatic symptoms; Cognitive symptoms; Multidimensional anxiety theory